RITUAL PEMBAKARAN MAYAT (WAREKMA) PADA MASYARAKAT MUSLIM DANI - Ade Yamin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
When some Dani tribe, in Baliem Valley, Wamena, Papua, convert into moslem, one tradition that is still practiced by the community, eventhough not in part of moslem faith, is cremation of death person (warekma). By ethnographic research, this reality is traced and studied. The result is a description the phenomena, in terms of its history, how it practices. In fact this rite has three main functions, i.e. ritual function, social function and religious function. If that tradition wishes to changed, it should be available substitutions that more or less in line or same with before.